Percepções das condicionalidades nos programas de transferência de renda: o caso das beneficiárias do CRAS Morro Nova Cintra - Ramacciotti, Nathalia Nabor [UNIFESP] (2014)
Social Security appears in Europe in the twentieth century as a tool to address the structural inequalities in the workforce produced by capitalism. From the Washington Consensus, 1989, the World Bank has established guidelines for cash transfer programs for developing countries. Brazilian programs, following these guidelines, are focal programs and intend to increase the ?human capital? of the population through conditionalities in the areas of Health and Education. This dissertation aimed to investigate the effects of compliance with these conditionalities, especially gender related, through the speech of their beneficiaries at CRAS Morro Nova Cintra, Santos. It started from the hypothesis that by prioritizing the female figure as the main responsible for compliance with conditionalities there is the risk of negative impacts on the life of this subject. This is a quantitative-qualitative practical research with explanatory goals. Data collection was conducted through focus groups, survey of official texts and social records analysis. Data analysis was performed by Critical Discourse Analysis. Dialectical Materialism was the theoretical referential. Women surveyed perceive conditionality as charge, and although not directly resent it, point out that other participants who are not meeting the commitments, should be as charged as they are. The results also showed that the sexual division of labor appeared in the speeches collected in the focus groups, but not in the discourses of the state. Public policies do not act effectively to change this unfair situation, which may contribute to the maintenance of social inequality in Brazil.